2015
DOI: 10.1177/230949901502300121
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Arthroplasty Using a Short-Stem Prosthesis: Restoration of Hip Anatomy

Abstract: Purpose. To evaluate hip parameters such as vertical centre of rotation (VCR), horizontal centre of rotation (HCR), femoral offset, and leg length after total hip arthroplasty (THA) using the Nanos short-stem prosthesis. Methods. Medical records of 73 men and 74 women aged 25 to 92 (mean, 63) years who underwent THA using the Nanos short-stem prosthesis by a single surgeon were reviewed. Prior to the surgery, the optimal cup and stem size, head length, and level of the neck osteotomy were determined using radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
1
6
0
3
Order By: Relevance
“…Moreover, all of them are related to long stem implants. In this study, the optimal performance was found using a hip implant with a total length smaller than 120 mm; confirming the potential advantages of the short stems [ 50 ]. For the parameter characterizing the implant length in contact with the bone (D), optimal designs resulted in values smaller than 50%.…”
Section: - Discussionsupporting
confidence: 65%
“…Moreover, all of them are related to long stem implants. In this study, the optimal performance was found using a hip implant with a total length smaller than 120 mm; confirming the potential advantages of the short stems [ 50 ]. For the parameter characterizing the implant length in contact with the bone (D), optimal designs resulted in values smaller than 50%.…”
Section: - Discussionsupporting
confidence: 65%
“…Aus diesem Grund ist die Weiterentwicklung der minimalinvasiven OP-Techniken mit Muskelerhalt notwendig, dies erfordert jedoch modifizierte und neue Implantate, welche diese OP-Techniken ermöglichen [2 -5]. Der Einsatz der totalen Hüftendoprothese hat sich weiterentwickelt von der ausschließlichen Versorgung geriatrischer Patienten hin zu einem jungen und aktiven Patientengut [3,4,6]. Das Langzeitüberleben der konventionellen Designs ist hinreichend und gut dokumentiert, da jedoch bei den jüngeren Patienten die Wahrscheinlichkeit einer notwendigen Revision ansteigt, ist es zu einer Weiterentwicklung der Langschaftprothesen gekommen [1].…”
Section: Finite Element Analysis and Biomechanical Testing Of The Newunclassified
“…Das Langzeitüberleben der konventionellen Designs ist hinreichend und gut dokumentiert, da jedoch bei den jüngeren Patienten die Wahrscheinlichkeit einer notwendigen Revision ansteigt, ist es zu einer Weiterentwicklung der Langschaftprothesen gekommen [1]. Seit Anfang der 1990er-Jahre werden kürzere Implantate entwickelt, um bei ausreichender biomechanischer Verankerung mehr Knochen für spätere Revisionen zu erhalten [6,7]. Es wurden deshalb die Schäfte laufend modifiziert, wobei die schenkelhalsteilerhaltenden Kurzschaftprothesen einen guten Kompromiss für die minimalinvasive Versorgung darstellen.…”
Section: Finite Element Analysis and Biomechanical Testing Of The Newunclassified
“…Jobb mozgástartományt, jobb funkcionális eredményt, stabilitást és kevesebb kopást eredményez. Ezért a műtét előttivel megegyező, vagy nagyobb offset az ajánlott (1).…”
Section: Bevezetésunclassified